CONSERVATION STATUS AND RESEARCH ON PROPAGATION OF CAMELLIA PIQUETIANA IN LAM DONG PROVINCE, VIETNAM - Hong En Le; Quang Cuong Truong; Van Cam Ngo; Pham Doan Nguyen; Van Phuc Nguyen; Van Duong Do; Thi Thuy Hoa Le; Si Hung Ho; Ba Trung Nguyen; Giang Phi Ngo; Thi Phuong Ho (Tạp chí Khoa học Đại học Đà Lạt)
Camellia piquetiana, one of the endemic species of Vietnam, is classified as Critically Endangered (CR) by the IUCN. A reassessment of its conservation status and research into propagation methods are essential for its conservation. Our survey recorded 246 mature individuals in the wild at three locations in Lam Dong Province: Bao Loc City, Bao Lam District, and Da Huoai District. The conservation assessment for this species, determined with GeoCat software, is still CR. Propagation by partially uncoated seeds had a higher propagation efficiency than by coated seeds. The germination percentage was 92.22%; the seeds began germination after 11 days and finished after 29.33 days. The results showed that stem cuttings immersed in a concentration of 500 ppm indole-3-butyric acid for 10 minutes with a 100% coir substrate gave the highest survival percentage (90.00%), rooting percentage (86.67%), average number of roots (4.54), root length (4.86 cm), and rooting index (21.98) after 90 days.